Solange te parle féministe. Sexe, genre et sexualité dans les capsules de Solange te parle - Isabelle Boisclair (Itinéraires)
Born in 1985 in Montreal, of a Romanian father and a Québécois mother, Ina Mihalache moved to France in 2004; she created the weblog Solange te parle in 2011. Five vignettes of her series will be analyzed regarding discourse, sex, sexuality, and gender representations. With her texts which question the social norms of the feminine, the masculine as well as that of sexual encounters, with her natural-looking self-staging, Mihalache scathingly undoes the hegemonic models, valuing crude/raw, more authentic-looking subjectivities and sexualities—thus reframing new identity possibles/possibilities.